The Influence of Entrepreneurship Education on University Students' Entrepreneurship Self-Efficacy and Entrepreneurial Intention - Vivekananth, Sarasaran; Indiran, Logaiswari; Umar Haiyat Abdul Kohar (Journal of Technical Education and Training, 2023)
Entrepreneurship education in Higher Learning Institutions (HLIs) is vital to strengthening a country’s entrepreneurship ecosystem, which fosters economic growth, innovation, and job creation. Through entrepreneurship education, more job creators are expected to be created and nurtured with entrepreneurial awareness, knowledge, abilities, and support. Therefore, this study investigated the relationship between entrepreneurship education, namely entrepreneurship curriculum, entrepreneurship lecturers’ competency, and university entrepreneurship support in influencing entrepreneurship intention among Universiti Teknologi Malaysia’s students, with entrepreneurship self-efficacy as the mediator. The methodological approach of this study is a quantitative method. The population of this study was Universiti Teknologi Malaysia (UTM) undergraduate students with a sample size of 212 respondents, obtained using simple random probability sampling. Data collected from respondents was analysed using the SPSS statistical analytical tool by applying descriptive, regression and mediation tests. The study’s findings revealed that entrepreneurship curriculum and university entrepreneurship support have significantly influenced both entrepreneurship self-efficacy and intention. However, entrepreneurship lecturers’ competency was found to have an insignificant relationship with entrepreneurship self-efficacy and intention. The influence of entrepreneurship self-efficacy towards entrepreneurship intention was also significant. Meanwhile, the mediating effect of entrepreneurship self-efficacy between entrepreneurship education components (curriculum, lecturers’ competency, and university entrepreneurship support) and entrepreneurship intention were all significant. Thus, this study has provided insights for various stakeholders, predominantly academicians, HLIs, and policymakers, to understand the current scenario on the effectiveness of Malaysia’s entrepreneurship education.